‘Watching out for my boo’: Understanding women’s aggression in a night-time economy - Swann, Rachel (Criminology & criminal justice, 2021)
Female aggression in night-time economies (NTE) is a relatively under-researched area of criminological inquiry. This article focuses on a group of White, working-class local women (Locals) drawing on a mixed-method qualitative study of 78 women (18–58 years) who participated in the NTE of a Welsh city centre. This article explores the women’s accounts and understandings of engaging in aggressive behaviours in this particular situational context. Foregrounding their voices, the research found that stereotypical assumptions surrounding the women’s reputation for unprovoked aggression is not supported. Rather, the women themselves understand their aggression as justifiable responses to breaches of shared group norms and values in relation to both reputation and manners. This group of women’s aggressive behaviour often was oriented towards maintaining their relationships and loyalty to each other and their group. This further challenges research in which women’s violence is framed as a response to or modelled on the behaviour of men. This article reports on a subgroup (‘Locals’) of a larger study that included two additional female groups, Professionals and Students, the perspectives of which are occasionally included to draw out distinctions with the working-class women focused on here.